Factors associated with improved outcomes in intensively treated early rheumatoid arthritis - Kuusalo, Laura (fi=Turun yliopisto|en=University of Turku|, 2018)
The cornerstone of the treatment of early rheumatoid arthritis (RA) is intensive, clinical remission targeted treatment with disease-modifying antirheumatic drugs (DMARDs). The aim of the present study was to elucidate factors which are, in addition to the drug treatment, associated with improved outcomes in early RA. In the New Finnish Rheumatoid Arthritis Combination Therapy (NEO-RACo) trial, 99 patients with early RA were treated with three DMARDs, low-dose oral prednisolone, and intra-articular glucocorticoid injections (iaGCs) to swollen joints for 2 years. They were randomized to receive either infliximab or placebo infusions for the initial six-month period, and were followed up for five years. The aim of treatment was a strict remission with no swollen or tender joints. We assessed the influence of selected physician-related (I, II) and patient-related (III, IV) factors upon outcomes. These included the physicians’ adherence to targeted treatment (I), neglected iaGC injections (II), the burden of adverse events (III), and the associations between baseline patient-reported outcomes (PROs) and two-year remission (IV). Greater physicians’ adherence was associated with higher remission rates and lower disease activity during the 2–5 year follow-up period (I). Patients initially treated with greater adherence required fewer biologic DMARDs and changes in medication during the follow-up period. Patients who did not receive intraarticular GCs to all swollen joints were less likely to achieve remission, had higher disease activity, and suffered from a lower quality of life at 2 years’ follow-up (II). A high burden of adverse events during the first year was associated with higher disease activity and reduced remission rates at one and two years (III). Only two of the eleven assessed PROs, the vitality and role-emotional functioning sections of the Short Form 36 questionnaire were associated with an increased likelihood of remission (IV). In conclusion, physicians’ adherence to the targeted treatment should be optimized and all swollen joints treated with iaGCs to bring as many early RA patients as possible into remission. Certain PROs and frequent adverse events may help in recognizing patients who are less likely to achieve remission.

Intensiivisesti hoidetun varhaisen nivelreuman hyvään hoitotulokseen vaikuttavat tekijät Varhaisen nivelreuman hoidon kulmakivi on tehokas, kliiniseen remissioon tähtäävä reumalääkehoito. Väitöskirjatyön tavoittena oli selvittää, mitkä tekijät intensiivisen antireumaattihoidon lisäksi vaikuttavat hyvän hoitotuloksen saavuttamiseen. Uusi suomalainen nivelreuman kombinaatiohoito (NEO-REKO) –tutkimuksessa 99 varhaista nivelreumaa sairastavaa potilasta hoidettin 2 vuotta kolmen synteettisen reumalääkkeen, prednisolonin ja nivelensisäisten glukokortikoidiinjektioiden (GI) yhdistelmällä ja satunnaistettiin saamaan joko infliksimabi- tai placebo-infuusioita 6 kuukautta. Seuranta jatkui viisi vuotta ja hoidon tavoite oli koko tämän ajan tiukka remissio ilman arkoja tai turvonneita niveliä. Arvioimme lääkärin hoitoon sitoutumisen (I), kaikkien tulehtuneiden nivelten GI:lla hoitamatta jättämisen (II), ja ensimmäisen vuoden aikana koettujen haittatapahtumien aiheuttaman taakan (III) vaikutuksen useisiin päätemuuttujiin. Lisäksi tutkimme, voidaanko remission saavuttamista ennustaa diagnoosivaiheen potilaslähtöisten mittareiden avulla (IV). Osoitimme, että lääkärin sitoutuminen hoitoprotokollaan oli yhteydessä korkeampiin remissiolukemiin, matalampaan nivelreuman aktiivisuuteen, ja pienempään lääkitystehostusten ja biologisten lääkkeiden tarpeeseen 2–5 vuoden seurannassa (I). Jos GI:t kaikkiin turvonneisiin niveliin jätettiin antamatta, saavuttivat potilaat remission epätodennäköisemmin, heidän nivelreumansa aktiivisuus oli korkeampi ja elämänlaatunsa huonompi (II). Korkea haittatapahtumataakka oli yhteydessä korkeampaan tautiaktiivisuuteen ja matalampiin remissiolukemiin 1 ja 2 vuoden kuluttua (III). Lähtötilanteessa tutkituista yhdestätoista potilaslähtöisestä mittarista kaksi, Short Form 36 kyselyllä mitatut vitaliteetti ja emotionaalinen roolitoiminta, olivat yhteydessä suurempaan remission saavuttamisen todennäköisyyteen kahden vuoden kohdalla (IV). Varhaisen nivelreuman hoitotulosten parantamiseksi myös lääkäreiden hoitoon sitoutuminen tulee optimoida. Glukokortikoidia tulee injisoida kaikkiin tulehtuneisiin niveliin. Tietyt potilaslähtöiset mittarit ja potilaan korkea haittatapahtumataakka saattavat auttaa niiden potilaiden tunnistamisessa, joilla on alentunut remission saavuttamiset todennäköisyys.